2015
DOI: 10.1371/journal.pbio.1002276
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Feel Sick When Infected—Can Altruism Play a Role?

Abstract: When we contract an infection, we typically feel sick and behave accordingly. Symptoms of sickness behavior (SB) include anorexia, hypersomnia, depression, and reduced social interactions. SB affects species spanning from arthropods to vertebrates, is triggered nonspecifically by viruses, bacteria, and parasites, and is orchestrated by a complex network of cytokines and neuroendocrine pathways; clearly, it has been naturally selected. Nonetheless, SB seems evolutionarily costly: it promotes starvation and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 89 publications
(114 reference statements)
4
103
1
Order By: Relevance
“…For example, several snake carcasses found near an infected hibernaculum were thought to have prematurely emerged from the den site and succumbed to night-time frosts (the electronic supplementary material). Additional research focused on the relationship between host body temperature and SFD progression may explain why infected snakes exhibit unusual behaviours and whether such 'sickness behaviours' are effective in combatting infection as has been proposed in other animals [23].…”
Section: Pathogenesismentioning
confidence: 99%
“…For example, several snake carcasses found near an infected hibernaculum were thought to have prematurely emerged from the den site and succumbed to night-time frosts (the electronic supplementary material). Additional research focused on the relationship between host body temperature and SFD progression may explain why infected snakes exhibit unusual behaviours and whether such 'sickness behaviours' are effective in combatting infection as has been proposed in other animals [23].…”
Section: Pathogenesismentioning
confidence: 99%
“…In 1988, Hart 81 first argued that sickness behaviour is not a maladaptive response to infection but rather a coordinated behavioural strategy to promote host survival. A more recent hypothesis attributes sickness behaviour to altruism and kin selection 82 ; that is, sickness behaviour provides an evolutionary advantage to survival of the herd 83,84 . Interestingly, it has been reported that, if the infected host does not elicit overt sickness behaviour, they may increase their propensity to aggregate 85 .…”
Section: A Virus-versus-host Competitionmentioning
confidence: 99%
“…In order to see if activation of the host immune system plays a role in the behavioural changes (i.e. sickness behaviour; Shakhar and Shakhar, 2015;Hart, 1988), we administered LPS (Pepels et al, 2004) to non-parasitized sticklebacks. LPS is known to create an in vitro immune response from stickleback head kidney leukocytes that is similar to the response measured by exposing the same cell line to S. solidus tissues (Scharsack et al, 2013).…”
Section: Introductionmentioning
confidence: 99%